Nano-Structured Porous Yttria-Stabilized Zirconia Membrane for High-Temperature CO 2 Capture from H 2/ CO 2 Mixture - Shah, S.H. (Springer Verlag, 2016)
A yttria-stabilized zirconia (YSZ, 8 mol Y 2O 3) membrane was prepared employing zirconium n-propoxide as a precursor via solâgel method. Unlike conventional methods, hydrolyzing water was slowly released in this method through esterification of 1-propanol and glacial acetic acid. X-ray diffraction verified that YSZ membrane was partially transformed to the tetragonal phase. Ten times dip-coated membrane thickness was about 742Â nm, determined by field emission scanning electron microscopy (FE-SEM) micrograph. BrunauerâEmmetâTeller measured average pore size of unsupported YSZ from gas adsorption and desorption indicating two modes centered at 2.66 and 2.38Â nm. Crystallite size (D) as calculated from Scherrerâs equation was 6.8, 12.23, and 13.61Â nm for unsupported YSZ powder before and after calcination, respectively, at 25, 500, and 600âC. Thermogravimetric analysis showed that the mass loss of the samples calcined at temperatures higher than 600âC had no significant differences indicating the completion of loss of organics. Supported YSZ membrane was tested by a gas permeation apparatus. The single gas permeance of YSZ membrane including Î± - Al 2O 3 was measured as 14.89 Ã 10 - 6 and 1.75Ã10-6molm-2s-1Pa-1 for H 2 and CO 2 at 300âC, respectively. Permeance of H 2 and CO 2 through YSZ in 75:25 H 2/CO 2 binary feed mixture was 9.696 Ã 10 - 6 and 0.97Ã10-6molm-2s-1Pa-1, respectively, at 300âC. The selectivity of hydrogen in YSZ was 10. It was concluded that the membrane was highly promising for the separation of H 2/ CO 2 mixture from various H 2-containing process streams under steam environment for high-temperature separation. Â© 2016, King Fahd University of Petroleum & Minerals.